PERLINDUNGAN HUKUM TERHADAP PEKERJA KONTRAK DALAM PERJANJIAN KERJA DENGAN SISTEM OUTSOURCING DI INDONESIA - Pandhu Maruli Yoso; " Suraji (Jurnal Privat Law, 2023)
This article aims to determine the concept and examine the relationship between agency workers and companies involved in work agreements with the outsourcing system in Indonesia. There is a legal vacuum in defining this work relationship that gives more benefits to the company, which on the other hand also creates problems related to the protection of agency workers' rights. This research is a normative legal research. The approach used by the author is the statutory approach, case approach and the conceptual approach. The sources of law used consist of primary and secondary legal materials. The data collection technique used by the writer is a library research obtained from a review of legal regulations related to outsourcing contract workers. The technique of analyzing legal materials uses the syllogistic method with a deductive mindset. The result of this study is that with the existence of a legal vacuum in defining a legal relationship, the work agreement must have legal certainty in accordance with the work agreement arrangement in the outsourcing system and the agreement principle in the work agreement itself. This is intended so that contract workers and companies in the outsourcing system can mutually fulfill their rights and obligations according to the binding agreement of each party.